Translation of plasma technology from the lab to the food industry - Cullen, P.J.; Lalor, James; Scally, Laurence; Boehm, Daniela; Milosavljević, Vladimir; Bourke, Paula; Keener, Kevin (Wiley-VCH Verlag, 2017)
The potential of cold plasma as a food processing aid has been demonstrated for a range of processes and products. The potential applications of plasma technology are extensive and include: microbial decontamination, pest control, toxin elimination, food and package functionalisation and many others. However, studies reported to date have principally been at laboratory scale. This paper discusses the status and challenges of transferring the technology to the industry. The major challenges discussed for adoption of atmospheric plasma as a food processing tool by industry are: 1) demonstration of product/process specific efficacies; 2) development of process compatible technology designs and scale-up; 3) effective process control and validation; 4) regulatory approval and 5) consumer acceptance.